Assessment of Specific Methanogenic Activity from Cow Dung - Abdul Malik, Izza; Fadzil, Farizah; Fadzil, Farihah; Seswoya, Roslinda (International Journal of Integrated Engineering, 2022)
The specific methanogenic activity (SMA) is a test to measure the producing potential of an anaerobic bacteria until it’s allowing a relevant organic loading rates to be applied for a selected substrate. Commonly, acetate is used as substrate for the SMA test. Anaerobic bacteria were mostly taken from an anaerobic digester and cow dung was also implemented as a source of an anaerobic bacteria. However, the results of SMA of cow dung was less reported. Therefore, this study is initiated to determine the potential of methane production from the cow dung by using the SMA test. Prior the SMA test, the cow dung was characterized for solids where the results showed that the cow dung is having 12.00 g L-1 for total solid and 10.50 g L-1 for volatile solid. The SMA test was conducted at mesophilic condition by using an automatic methane potential system test (AMPTS II) and the SMA of the cow dung was found as 0.04 in unit g COD-CH4 g-1VS-1d-1. The significance of this research is to determine the anaerobic bacteria potential of cow dung for use in the anaerobic digestion process, which offers numerous advantages for manufacturing, particularly in industrial applications such as methane production (fuel).